Metabolic processes of prostaglandin metabolism in women at 28–30 weeks of gestation with COVID-19 - N. A. Ishutina; I. A. Andrievskaya (Acta Biomedica Scientifica, 2024)
Background. COVID-19 negatively impacts pregnancy progression and outcomes. However, data regarding pregnancy complications related to prostaglandin activity during COVID-19 remain insufficient.The aim. To assess markers of metabolic processes related to prostaglandin metabolism in the blood of pregnant women depending on the severity of COVID-19 and to explore associations with the development of pregnancy complications.Methods. The study included 109 pregnant women in their third trimester (28–30 weeks), 36 of whom had mild COVID-19, 38 had moderate COVID-19, and 35 were not infected with SARS-CoV-2. The concentration of prostaglandins E2 and F2α, phospholipase A2 (PLA2), cyclooxygenase 2 (COX2), and arachidonic acid (AA) were measured in the blood using enzyme-linked immunosorbent assays and gasliquid chromatography for AA.Results. Comparative analysis showed that pregnant women with moderate COVID-19 had significantly higher levels of AA, COX2, PLA2, prostaglandins E2 and F2α (p < 0.0001) compared to those with mild disease. These women also experienced more frequent complications, such as chronic placental insufficiency, preterm labor, and premature rupture of membranes. Regression analysis revealed associations between chronic placental insufficiency and prostaglandin E2 levels (p < 0.0001), preterm labor, AA (p = 0.001) and COX2 (p = 0.001); premature rupture of membranes and PLA2 (p = 0.025), COX2 (p < 0.001), AA (p < 0.001).Conclusion. Moderate COVID-19 during the third trimester of pregnancy is associated with increased levels of AA, COX2, PLA2, and prostaglandins E2 and F2α in the blood. The most significant factors increasing the risk of pregnancy complications in women with moderate COVID-19 were elevated levels of AA, COX2, and prostaglandin E2 in the blood.